Russia Economic Report, November 2018 : Preserving Stability, Doubling Growth, Halving Poverty – How? - World Bank Group (World Bank, Washington, DC, 2019)
Global growth is broadly stable but downside risks from rising trade tensions are increasing.A weakening recovery in trade and manufacturing activities is weighing down global growth. Global goods trade has decelerated more rapidly than expected. U.S. tariff s and the retaliatoryresponses of its trading partners have affected 2.5 percent of global goods imports. Surveys ofcompanies in the U.S., China and Japan suggest that the risks of a trade war have not yet fullymaterialized. While the Eurasian Union (excluding Russia) posted strong growth in 2018, Russia'smain trading partners – the Euro area and China – experienced a growth slowdown. Financial conditions for Emerging Markets and Developing Economies (EMDEs) are tightening. Divergent monetary policies and growth prospects among the U.S. and other major economies contributed to a significant appreciation of the U.S. dollar in 2018. This, together with intensifying trade tensions, deteriorating growth prospects and renewed attention to external vulnerabilities has contributed to significant depreciations and capital outflows in many EMDEs. EMDE currencies fell – including the Russian ruble – and cumulative portfolio outflows from EMDEs surpassed those seen after the 2013 taper tantrum. Economies with external vulnerabilities, including Argentina, Indonesia, and Turkey, experienced the sharpest currency depreciations. While the spillover from those countries has been limited, the intensification of turmoil could lead investors to reevaluate their exposure to EMDEs and to capital outflows.